2018
DOI: 10.1016/j.kjms.2018.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Mir‐483 inhibits colon cancer cell proliferation and migration by targeting TRAF1

Abstract: MicroRNAs are important regulators during human growth and development. Emerging evidence indicates that microRNAs play important roles in colorectal cancer. The aim of this study is to reveal the biological function and direct target gene of miR-483 in colorectal cancer. The biological function of miR-483 on the proliferation and migration of colon cancer cells was then examined by Edu assay and transwell assay, respectively. Our findings revealed that miR-483 mimic could significantly inhibit cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…MiR-483-3p is underexpressed in breast cancer [28, 29], colon cancer [30], and gastric cancer [30]. In our study, we also demonstrated that miR-483-3p is downregulated in OS tissues and cell lines.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…MiR-483-3p is underexpressed in breast cancer [28, 29], colon cancer [30], and gastric cancer [30]. In our study, we also demonstrated that miR-483-3p is downregulated in OS tissues and cell lines.…”
Section: Discussionsupporting
confidence: 72%
“…After screening for miRNAs using the online software starBase 3.0, miR-483-3p was predicted to be a potential target of NR2F1-AS1 (Figure 3B). MiR-483-3p was chosen for further experimental validation because of its known tumor-suppressive actions in multiple types of human cancers [2830]. To verify this, a luciferase reporter assay was carried out in HOS and U2OS cells after cotransfection with either NR2F1-AS1-wt or NR2F1-AS1-mut and either agomir-483-3p or agomir-NC.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpressed miR‐483‐5p could inhibit proliferation and metastasis of renal cancer cells, and increase the expression of E‐cadherin, and reduce the expression of N‐cadherin to reverse EMT process. Niu et al certificated that miR‐483 mimic could inhibit proliferation and migration of colorectal cancer cell 38 . Menbari et al confirmed that miR‐483‐3p could suppress the proliferation and progression in breast cancer cells 39 .…”
Section: Discussionmentioning
confidence: 99%
“…25 A previous study has demonstrated that miR-483 inhibited cell proliferation and migration in colon cancer. 26 Wang et al have indicated that miR-483 suppressed the proliferation of glioma cells. 27 However, the effect of miR-483 in glioma was still unknown.…”
Section: Discussionmentioning
confidence: 99%